On a General Subclass of q-Starlike and q-Convex Analytic Functions (Contemporary Mathematics, 2024)
We introduce a certain subclass of analytic functions in the open unit disk U involving the q-derivative operator. Some convolution results and Fekete-Szegö inequalities for the analytic functions belonging to this class are derived. We have also provided some results as corollaries of our theorems.
Keywords: univalent function; convolution; q-starlike; q-convex; fekete-szegö problem